2019
DOI: 10.1186/s12989-019-0300-x
|View full text |Cite
|
Sign up to set email alerts
|

Silica nanoparticles trigger the vascular endothelial dysfunction and prethrombotic state via miR-451 directly regulating the IL6R signaling pathway

Abstract: Background Safety evaluation is a prerequisite for nanomaterials in a wide range of fields, including chemical industries, medicine or food sciences. Previously, we had demonstrated that SiNPs could trigger the thrombotic effects in vivo, but the underlying mechanisms remain unknown. This study was aimed to explore and verify the role of miR-451a on SiNPs-induced vascular endothelial dysfunction and pre-thrombotic state. Results The color doppler ultrasound results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 40 publications
(41 reference statements)
2
23
0
2
Order By: Relevance
“…Endothelial injury and blood exposure to collagen beneath the endothelium can activate factor XII (Hageman factor) and trigger blood coagulation via the intrinsic coagulation pathway (contact pathway) [41]. Intravascular coagulation may be triggered by endothelial injury/exfoliation, collagen exposure, and initiation of the contact pathway after exposure to SiNPs [42], and/or by changing the levels and activities of coagulant factors, anticoagulants and platelets as previously reported [43][44][45]. Although the pro-coagulation effect of SiNPs was not initially found in the present study, we found impressive intravascular coagulation in multiple organs after in vivo exposure to SiNPs.…”
Section: Discussionmentioning
confidence: 73%
“…Endothelial injury and blood exposure to collagen beneath the endothelium can activate factor XII (Hageman factor) and trigger blood coagulation via the intrinsic coagulation pathway (contact pathway) [41]. Intravascular coagulation may be triggered by endothelial injury/exfoliation, collagen exposure, and initiation of the contact pathway after exposure to SiNPs [42], and/or by changing the levels and activities of coagulant factors, anticoagulants and platelets as previously reported [43][44][45]. Although the pro-coagulation effect of SiNPs was not initially found in the present study, we found impressive intravascular coagulation in multiple organs after in vivo exposure to SiNPs.…”
Section: Discussionmentioning
confidence: 73%
“…We firstly administered Western diet-fed ApoE −/− mice with SiNPs through intratracheal instillation for 12 weeks by mimicking occupational scenario, and UBM was applied to monitor the development and progression of atherosclerosis. Currently, only few studies have reported the vascular effects of NPs through Doppler ultrasound trace [31]. As a result, the data indicated the atherosclerosis model was well established, and SiNPs exposure reduced arterial elasticity, aggravated the arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…We rstly administered Western diet-fed ApoE -/mice with SiNPs or saline through intratracheal instillation for 12 weeks, and UBM was applied to monitor the development and progression of atherosclerosis. Currently, only few studies have reported the vascular effects of NPs through Doppler ultrasound trace [32]. As a result, the data indicated the atherosclerosis model was well established, and SiNPs exposure reduced arterial elasticity, aggravated the arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a discontinued or fragmented intimal surface was induced by repeated pulmonary exposure of SiNPs, accompanied with endothelial apoptosis [27]. In addition, the ability to induce thrombosis formation may also attribute to the pro-atherogenic potential of SiNPs [32]. However, the underlying mechanisms by which SiNPs in uenced atherogenesis still remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%